Engineering 3D Cobalt-MOF/CNF Composites for Enhanced Alkaline Water Splitting - Pavithra Suresh; Abirami Natarajan; Arulmozhi Rajaram (Chemical and Materials Sciences: Research Findings Vol. 1, 2025)
This study presents the synthesis and characterization of a novel three-dimensional Cobalt-MOF/Carbon Nanofiber (Co-MOF/CNF) composite for enhanced electrocatalytic applications. Structural and morphological analyses were performed using scanning electron microscopy (SEM), X-ray diffraction (XRD), and Fourier-transform infrared spectroscopy (FTIR). SEM images confirm the uniform integration of Co-MOF with the CNF network, forming a highly porous and interconnected structure that facilitates efficient charge transfer. XRD patterns reveal the successful incorporation of Co-MOF, with characteristic diffraction peaks indicating high crystallinity and phase purity. FTIR spectra further confirm the presence of functional groups associated with imidazole ligands and carbon-based frameworks, highlighting the structural integrity of the composite. The Co-MOF/CNF composite demonstrates superior electrochemical performance, attributed to its enhanced conductivity and active surface area. These findings underscore its potential for sustainable energy applications, particularly in electrochemical water splitting.